ANALISIS GAYA BELAJAR PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA KELAS 1 DI SD NEGERI PETOMPON 02 SEMARANG - Dewi Ayu Wulandari; Choirul Huda; Sri Suneki (STKIP Subang, 2023)
Students' learning styles in learning vary, so it is important for teachers to know the learning styles of their students. There are students who feel that mathematics is difficult to understand and understand, and teachers do not know student learning styles. One of the characteristics of learning that is related to the acquisition, processing, and transfer of knowledge is the student's learning style. The purpose of this study is to determine students' learning styles when learning mathematics. Learning style is a very important form of learning. Information related to the characteristics of student learning styles, it is very important for teachers to improve the quality of learning. The research method is qualitative research. Data collection techniques through interviews, observation and documentation. Data validity was carried out through technique and source triangulation. The data analysis technique used consists of data acquisition, data reduction, data presentation and drawing conclusions. The results showed that the learning style of grade 1 students at SD Negeri Petompon 02 Semarang in learning mathematics, which showed visual characteristics had visual characteristics, namely students could understand problems by reading, which they themselves could not. The auditory learning style means that students understand better when the teacher reads the questions, knows how to convey information obtained from their work orally. A learning style with kinesthetic characteristics, namely students prefer to solve problems in groups, cannot concentrate on solving problems if they have to sit still for a long time. The results showed that the learning style of grade 1 students at SD Negeri Petompon 02 Semarang was a learning style. visual, auditory, kinesthetic and the most dominant learning style is the kinesthetic learning style.